(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
In the current context of the banking system development, the quality of the commercial banks’ loan portfolio is of key importance for ensuring financial stability and minimizing credit risks. One of the main tools for credit risk management are credit scoring models, which allow for an objective assessment of borrowers’ solvency. The purpose of this article is to comprehensively assess the impact of credit scoring models on the quality of the commercial banks’ loan portfolio. The paper examines the theoretical foundations of loan portfolio formation, the nature and types of credit scoring models, and analyzes their role in reducing the level of overdue debt and improving the efficiency of banks’ lending activities. Particular attention is paid to the relationship between validated scoring models and key indicators of loan portfolio quality.